Repopulation of an auricular cartilage scaffold, AuriScaff, perforated with an enzyme combination. (1st March 2019) - Nürnberger, S.; Schneider, C.; van Osch, G.V.M.; Keibl, C.; Rieder, B.; Monforte, X.; Teuschl, A.H.; Mühleder, S.; Holnthoner, W.; Schädl, B.; Gahleitner, C.; Redl, H.; et al.
Graphical abstract: Abstract: Biomaterials currently in use for articular cartilage regeneration do not mimic the composition or architecture of hyaline cartilage, leading to the formation of repair tissue with inferior characteristics. In this study we demonstrate the use of " AuriScaff ", an enzymatically perforated bovine auricular cartilage scaffold, as a novel biomaterial for repopulation with regenerative cells and for the formation of high-quality hyaline cartilage. AuriScaff features a traversing channel network, generated by selective depletion of elastic fibers, enabling uniform repopulation with therapeutic cells. The complex collagen type II matrix is left intact, as observed by immunohistochemistry, SEM and TEM. The compressive modulus is diminished, but three times higher than in the clinically used collagen type I/III scaffold that served as control. Seeding tests with human articular chondrocytes (hAC) alone and in co-culture with human adipose-derived stromal/stem cells (ASC) confirmed that the network enabled cell migration throughout the scaffold. It also guides collagen alignment along the channels and, due to the generally traverse channel alignment, newly deposited cartilage matrix corresponds with the orientation of collagen within articular cartilage. In an osteochondral plug model, AuriScaff filled the complete defect with compact collagen type II matrix and enabled chondrogenic differentiation inside the channels. Using adult articular chondrocytes from bovine origin (bAC), filling of even deep defects with high-quality hyaline-like cartilage was achieved after 6 weeks in vivo . With its composition and spatial organization, AuriScaff provides an optimal chondrogenic environment for therapeutic cells to treat cartilage defects and is expected to improve long-term outcome by channel-guided repopulation followed by matrix deposition and alignment. Statement of Significance: After two decades of tissue engineering for cartilage regeneration, there is still no optimal strategy available to overcome problems such as inconsistent clinical outcome, early and late graft failures. Especially large defects are dependent on biomaterials and their scaffolding, guiding and protective function. Considering the currently used biomaterials, structure and mechanical properties appear to be insufficient to fulfill this task. The novel scaffold developed within this study is the first approach enabling the use of dense cartilage matrix, repopulate it via channels and provide the cells with a compact collagen type II environment. Due to its density, it also provides better mechanical properties than materials currently used in clinics. We therefore think, that the auricular cartilage scaffold ( AuriScaff ) has a high potential to improve future cartilage regeneration approaches.